2017
DOI: 10.1039/c7ra09974f
|View full text |Cite
|
Sign up to set email alerts
|

A bifunctional two dimensional TM3(HHTP)2monolayer and its variations for oxygen electrode reactions

Abstract: To achieve renewable energy technologies, low-cost electrocatalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are required to replace Pt and IrO2/RuO2 catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The CHE model has been successfully applied for developing the novel electrocatalysts with prominent ORR performances, where the DFT calculations are in line with the experimental results (Nørskov et al, 2004 ; Greeley et al, 2009 ; Favaro et al, 2015 ; Lang et al, 2015 ; Jia et al, 2016 ; Tang et al, 2016 ; Liu et al, 2017 ; Li et al, 2018 ; Xu et al, 2018 ). Furthermore, the PBE/DNP method in Dmol 3 code has been widely employed for evaluating the potential of the TM-based carbon electrocatalysts (Wang et al, 2015 , 2016b ; Hou et al, 2016 ; Xiao et al, 2017 ). Therefore, the reliability of the mentioned approach is confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The CHE model has been successfully applied for developing the novel electrocatalysts with prominent ORR performances, where the DFT calculations are in line with the experimental results (Nørskov et al, 2004 ; Greeley et al, 2009 ; Favaro et al, 2015 ; Lang et al, 2015 ; Jia et al, 2016 ; Tang et al, 2016 ; Liu et al, 2017 ; Li et al, 2018 ; Xu et al, 2018 ). Furthermore, the PBE/DNP method in Dmol 3 code has been widely employed for evaluating the potential of the TM-based carbon electrocatalysts (Wang et al, 2015 , 2016b ; Hou et al, 2016 ; Xiao et al, 2017 ). Therefore, the reliability of the mentioned approach is confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The conductive MOFs composed of aromatic ring backbone with specific functional groups coordinated to metal ions effectively catalyze the ORR and/or OER 97 . Work by Jiang et al 98 shows the catalytic activity of conductive TM 3 (HHTP) 2 (TM = Fe, Co, Ni) and its variants of TMX 4 (X = O, S, Se) on bifunctional ORR/OER using the density functional theory (DFT) calculations 98 . It is found that the adsorption capacity of TM 3 (HHTP) 2 is mainly determined by the metal center (in the order of Fe > Co > Ni), while the ligand shows less effects.…”
Section: Conductive Mofs Towards Electrochemical Energy‐related Applimentioning
confidence: 99%
“…97 Work by Jiang et al 98 shows the catalytic activity of conductive TM 3 (HHTP) 2 (TM = Fe, Co, Ni) and its variants of TMX 4 (X = O, S, Se) on bifunctional ORR/OER using the density functional theory (DFT) calculations. 98 It is found that the adsorption capacity of TM 3 (HHTP) 2 is mainly determined by the metal center (in the order of Fe > Co > Ni), while the ligand shows less effects. Meanwhile, such bimetallic conductive MOFs are also an effective catalyst for the ORR.…”
Section: Electrocatalysismentioning
confidence: 99%
“…Inspired by the MN 4 motif of porphyrins as an active site [226] or embedded MN 2 in g‐C 3 N 4 for efficient oxygen electrode reactions, [227] Xiao et al. demonstrated the ability of MX 4 motif (where M=Fe, Co, Ni, X=O, S, Se) of extended triphenylene monolayer as an electrocatalyst for bifunctional ORR/OER activities [228] . The DFT study showed the metal dominancy on adsorption in the order of Fe>Co>Ni, with minor contribution stemming from the ligands.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%